Analysis Of Incidence Of Rubella Measles In The Working Area Of The Belimbing Health Center, Padang City In 2022 - Fuji Rahayu Henafi; Joserizal Serudji; Hardisman Hardisman (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Measles and rubella have long-term health consequences for an estimated 103,000 babies born with congenital rubella syndrome (CRS). A total of 541 cases of measles were found in districts and cities in West Sumatra with the highest number in the city of Padang in 2022. The aim of the study was to analyze the incidence of measles rubella in the working area of the Belimbing Health Center, Padang City in 2022. The research was conducted using a qualitative approach, the method used in this research are in-depth interviews, observation, and document review. The research was conducted in the Work Area of the Belimbing Health Center, Padang City. Informants consisted of 24 people consisting of 8 health workers, 5 cadres, and 11 mothers with children. The results of this study indicate mothers' knowledge about measles rubella is still not optimal. MR immunization has not reached the target as expected, there are still many parents who do not want to bring their children MR immunization, such as being consumed by HOAX news or gossip circulating about MR immunization, Surveillance in reporting MR cases is always reported every day if there are cases, surveillance officers trace cases and evaluate them, and the results of the report are submitted monthly to the P2P section of the Padang City Health Office. Most children suffer from measles because they get it from their playmates at school. The implication of this research is as an illustration of Incidence Of Rubella Measles In The Working Area Of The Belimbing Health Center, Padang City In 2022. Keywords: Health Center, Infection Disease, Measles, Padang City, Rubella